Inside Cover: Effects of Crystal Quality and Morphology on the Mechanical Performance of LLM‐105 Based PBXs (Prop., Explos., Pyrotech. 10/2019). Issue 10 (22nd October 2019) - Yang, Zhijian; Lin, Congmei; Gong, Feiyan; Zeng, Chengcheng; Zhang, Jianhu; Huang, Fenglei
Abstract : The cover picture shows the effects of crystal surface on the mechanical performance of LLM‐105 based PBXs. Crystals with high quality after recrystallization has poor tensile strength for PBXs, but can be visibly improved by acid treatment. Spherical morphology is profitable for both mechanical strength and creep resistance. Surface roughness has critical influence on the mechanical performance, because the anchor points created can be helpful for the bonding between energetic crystals and polymer matrix, thus increasing the interfacial strength and dimensional stability. Details are discussed in the article by Zhijian Yang, et al. on page 1219 ff.